Efektivitas metode pembelajaran daring terhadap hasil belajar kognitif materi bolavoli - Khaqim, Eef Abdurakhman; Wahyudi, Agung (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
Volleyball learning materials are transitioning from face-to-face learning to online learning. The purpose of this study was to find out how the implementation of online learning of volleyball material at MAN 1 Tegal and to find out how much effectiveness online learning had on cognitive learning outcomes. The type of data used is mixed methods research. The sample used is class X students at MAN 1 Tegal. At the quantitative stage of data collection using recap documentation, data analysis using the mean value. At the qualitative stage of data collection using interviews, data analysis using data reduction. Recapitulation of cognitive aspects of volleyball material obtained results of 100% of all respondents passing volleyball material with an average value of 73.31. The conclusion of this study is that the implementation of online learning for class X volleyball in MAN uses the emergency curriculum 13, there are many obstacles that hinder online learning, recap of the cognitive scores of 100% of all respondents passing the volleyball material with an average value of 73.31. Based on the results of this study, it can be seen that all deficiencies in the learning process during the COVID-19 pandemic are expected to be corrected, so that learning media can be found that are suitable for use in physical education learning.